Evolution of near- and far-field optical properties of Au bipyramids upon epitaxial deposition of Ag. Issue 9 (20th February 2020) - Xi, Min; Reinhard, Björn M.
Abstract : The effect of composition and tip morphology on the far-field optical response of Ag–Au–Ag nanorods with Au bipyramid core is quantified, and the near-field associated with standing plasmon waves in nanorods on silicon substrates is investigated. Abstract : Bimetallic plasmonic nanostructures provide composition and spatial distribution of the individual components in the nanostructure in addition to overall size and morphology as degrees of freedom for tuning near- and far-field optical responses. AgAuAg nanorods (NRs) generated through epitaxial deposition of Ag on the tips of Au bipyramids (BPs) are an important bimetallic model system whose longitudinal dipolar plasmon mode first shows a spectral blue-shift upon initial deposition of Ag on the Au BP tips followed by a red-shift after additional deposition of Ag. Here, we quantify the relative contributions from morphological and compositional effects to the far-field spectral shift of the longitudinal and vertical dipolar plasmon modes during the initial deposition of Ag and compare the near-field in Ag and AgAuAg NRs with lengths between L = 130 nm–280 nm under whitelight illumination through electromagnetic simulations. Subsequently, we experimentally characterize the near-field around AgAuAg NRs with lengths between L = 88.1–749.0 nm at a constant excitation wavelength of 1064 nm on a silicon (Si) support through scattering type near-field scanning microscopy (sNSOM). We detect Fabry–Perot resonance-like higher order multipolar plasmon resonances whose order and near-field pattern depends on the length and composition of the NRs as well as the refractive index of the ambient medium. We find that under oblique illumination higher order multipolar modes with an even symmetry dominate on the high refractive index Si substrate due to strong electromagnetic interactions between the NR and the substrate.